Growth, leaf gas exchange and secondary metabolites of orthosiphon stamineus as affected by multiwall carbon nanotubes application - Izad, Ayu Izera; Ibrahim, Mohd Hafiz; Che Abdullah, Che Azurahanim; Mohd Zain, Nurul Amalina (Sciencedomain International, 2018)
Aims: This study was conducted to study the growth, leaf gas exchange and secondary metabolites of Orthosiphon stamineus as affected by Multiwalled carbon nanotubes application (MWCNT). Study Design: Orthosiphon stamineus were exposed to four different multi-walled carbon nanotubes (MWCNTs) concentration (0, 700, 1400 and 2100 mg L-1). The experiment was organized in a randomized complete block (RCBD) design with three replications. Each experimental unit consisted of twelve plants, and there were a total of 144 plants used in the experiment. Place and Duration of Study: Department of Biology, Faculty of Science Universiti Putra Malaysia between November 2016 to March 2017. Methodology: Each plant was watered with 50 mL of MWCNTs solution in week 2 and 9. The leaves number were counted manually and the total plant biomass was taken by calculating the dry weight of root, stem, and leaf per seedling The total chlorophyll content in the leaves was measured using a SPAD chlorophyll meter. The leaf gas exchange was determined using LI6400XT portable photosynthesis system. Total phenolics and flavonoid were determined using Folin-Ciocalteu reagent. Results: It was found that application of MWCNTs would reduce the growth characteristics of this plant that was shown by decreased leaf numbers, total biomass and total chlorophyll content (TCC). As MWCNTs concentration increases from 0 > 2100 mg L-1, the leaf gas exchange parameter also shows reduced patterns. Generally, as the rate of MWCNTs increased from 700 > 2100 mg L-1 NWCNTs reduce the net photosynthesis (A), stomatal conductance (gs), transpiration rate (E) and increased the plant water use efficiency. The production of the secondary metabolites was directly dependable on MWCNTs concentration. As the rate was enhanced from 0 > 700 > 1400 > 2100 mg L-1 the production of total phenolics and flavonoids was enhanced. Conclusion: The current study revealed that the high application of MWCNTs concentration reduce the growth rate of O. stamineus, leaf gas exchange and simultaneously increase the production of secondary metabolites.